2014
DOI: 10.1016/j.optom.2013.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Visual functions and disability in diabetic retinopathy patients

Abstract: Impairment of near visual acuity, contrast sensitivity, and peripheral visual field correlated significantly with different types of visual disability. Hence, these clinical tests should be an integral part of the visual assessment of diabetic eyes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 19 publications
1
16
0
1
Order By: Relevance
“…A number of investigators have shown that diabetes affects visual function prior to the development of DR detectable by ophthalmoscopy. This includes deficits in contrast, 5 6 visual field 7 8 and colour vision sensitivity. 9 10 As such, amelioration of these visual function deficits may serve as an additional, useful biomarker for the onset and progression of retinopathy in patients with diabetes, yet no clinically evident DR, as well as those with established diabetes-induced retinal pathology.…”
Section: Introductionmentioning
confidence: 99%
“…A number of investigators have shown that diabetes affects visual function prior to the development of DR detectable by ophthalmoscopy. This includes deficits in contrast, 5 6 visual field 7 8 and colour vision sensitivity. 9 10 As such, amelioration of these visual function deficits may serve as an additional, useful biomarker for the onset and progression of retinopathy in patients with diabetes, yet no clinically evident DR, as well as those with established diabetes-induced retinal pathology.…”
Section: Introductionmentioning
confidence: 99%
“…Visual function deficit is among early ocular manifestations in diabetic patients [42,43]. The decline in visual responses including visual acuity and contrast sensitivity was documented in the mouse models of diabetic retinopathy and following retinal IR injury [5,44].…”
Section: Discussionmentioning
confidence: 99%
“…Asia, the global epicenter of the diabetic epidemic,3 is also facing an increasing number of patients with DME. Moreover, vision loss substantially compromises patients’ quality of life and capability of disease management 4. Therefore, effective treatments for DME are urgently needed.…”
Section: Introductionmentioning
confidence: 99%